1999
DOI: 10.1016/s0003-4975(98)01060-1
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary dirofilariasis

Abstract: Pulmonary dirofilariasis is a benign condition, transmitted by mosquitos to humans that results in peripheral pulmonary nodules. Awareness of this entity is important in the differential diagnosis of pulmonary coin lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 6 publications
1
22
0
1
Order By: Relevance
“…Numerous individual cases and several reviews with new cases have been reported from the United States, [1][2][3][16][17][18][19][20][21][22][23][24][25][26][27][28] Australia, 29,30 Japan, [31][32][33] and Spain. 34,35 In addition, the dirofilaria worm, though misidentified initially, has been reported in the heart 36 and the posterior vena cava.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous individual cases and several reviews with new cases have been reported from the United States, [1][2][3][16][17][18][19][20][21][22][23][24][25][26][27][28] Australia, 29,30 Japan, [31][32][33] and Spain. 34,35 In addition, the dirofilaria worm, though misidentified initially, has been reported in the heart 36 and the posterior vena cava.…”
Section: Discussionmentioning
confidence: 99%
“…D. immitis has also been associated with human dirofilariasis, as a result of accidental infection. Cases of human pulmonary dirofilariasis have been increasingly reported worldwide (Darrow and Lack, 1981;Echeverri et al, 1999;Foroulis et al, 2005). The first Korean case of human pulmonary and hepatic dirofilariasis was recently reported (Lee et al 2000;Kim et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…2,5,[9][10][11][12][13][14][15][16] Features differentiating the filarid in the rabbit in the current case from other filarid nematodes include size, the prominent r coelomyarian striated muscle, and the 2 prominent lateral cords with cuticular lateral ridges. Based on an excellent review of the diagnostic features of filarids in tissue section, other filarid parasites, including Dirofilaria tenuis, Dirofilaria repens, Dirofilaria ursi, Oncocerca spp., and Brugia spp., could be eliminated from consideration based on clearly identifiable differences from the parasite described herein.…”
Section: 459-16mentioning
confidence: 72%
“…1 The identity of this filarid as D. immitis using PCR analysis was unable to be conclusively confirmed, but much of the human and veterinary literature has used less stringent histomorphologic characteristics to diagnose D. immitis. 2,4,5,[9][10][11][12][13][14][15][16] Given the geographic location of this rabbit and the endemic prevalence of heartworm disease, the most likely diagnosis of the filarid is D. immitis.…”
Section: 459-16mentioning
confidence: 99%